Effects of an Atypical Antipsychotic, Zotepine, on Astroglial L-Glutamate Release through Hemichannels: Exploring the Mechanism of Mood-Stabilising Antipsychotic Actions and Antipsychotic-Induced Convulsion - Kouji Fukuyama; Motohiro Okada (MDPI AG, 2021)
Accumulating neuropsychopharmacological evidence has suggested that functional abnormalities of astroglial transmission and protein kinase B (Akt) contribute to the pathophysiology and/or pathomechanisms of several neuropsychiatric disorders, such as epilepsy, schizophrenia, affective disorders and antipsychotic-induced convulsions. Therefore, to explore the pathophysiology of mood-stabilising antipsychotics and the proconvulsive actions of atypical antipsychotics, the present study determined the effects of a mood-stabilising, atypical, antipsychotic agent, zotepine (ZTP), on astroglial L-glutamate release and the expression of connexin43 (Cx43) protein in cortical, primary, cultured astrocytes using ultra-high-pressure liquid chromatography and capillary immunoblotting systems. Both acute and subchronic administrations of therapeutically relevant concentrations of ZTP did not affect astroglial L-glutamate release or Cx43 expression in plasma membranes; however, chronic administration of a therapeutically relevant concentration of ZTP increased astroglial L-glutamate release and Cx43 expression in the plasma membrane. Subchronic administrations of a supratherapeutic concentration of ZTP enhanced astroglial L-glutamate release and Cx43 expression in the plasma membrane, whereas acute administration of a supratherapeutic concentration of ZTP enhanced astroglial L-glutamate release without affecting Cx43 expression. These stimulatory effects of ZTP on astroglial L-glutamate release through activated hemichannels and Cx43 trafficking to the astroglial plasma membrane were suppressed by the Akt inhibitor. These results suggest that ZTP enhances astroglial L-glutamate release in a concentration-dependent and time-dependent manner due to the enhanced function of astroglial hemichannels, probably via activation of Akt signalling. Therefore, the enhanced astroglial L-glutamatergic transmission induced by ZTP is, at least partially, involved in the mood-stabilising antipsychotic and proconvulsive actions of ZTP.